Pengaruh Inovasi Hijau, Pengungkapan Emisi Karbon, Dan Eko - Efisiensi Terhadap Nilai Perusahaan - Zidan Zahran; Alif Malik Muchlisin; Adriansyah Damara Putra; Christina Dwi Astuti (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to analyze the influence of Green Innovation, Carbon Emission Disclosure, and Eco-Efficiency on Firm Value in Consumer Cyclicals companies listed on the Indonesia Stock Exchange for the 2021–2025 period. This study employed a quantitative approach with secondary data obtained from Annual Reports and Sustainability Reports. Purposive sampling was used to select 76 companies with 368 observations after outlier management. Data analysis was performed using multiple linear regression with IBM SPSS.The results show that Green Innovation has a positive and significant effect on Firm Value. This finding indicates that implementing environmentally oriented innovation can increase investor confidence and strengthen firm value. Carbon Emission Disclosure has a significant effect on Firm Value, but in a negative direction. These results suggest that the market tends to interpret carbon emission disclosure as a signal of environmental risk, compliance costs, or potentially higher emissions management burdens. Meanwhile, Eco-Efficiency has no significant effect on Firm Value, indicating that eco-efficiency indicators such as ISO 14001 certification and PROPER ratings are not yet primary considerations for investors in assessing companies. Green Innovation, Carbon Emission Disclosure, and Eco-Efficiency simultaneously influence Corporate Value. This study concludes that environmental sustainability plays a role in shaping Corporate Value, although the influence of each dimension shows different results. This finding implies that companies need to strengthen the implementation of green innovation and environmental management strategies that can create economic value while enhancing positive market perception.